Skin Advanced Glycation End Products among Subjects with Type 2 Diabetes Mellitus with or without Distal Sensorimotor Polyneuropathy - Stella Papachristou; Kalliopi Pafili; Grigorios Trypsianis; Dimitrios Papazoglou; Konstantinos Vadikolias; Nikolaos Papanas (Journal of Diabetes Research)
Aim of the Study. To examine the correlation between skin AGEs and parameters of distal sensorimotor polyneuropathy (DSPN) in type 2 diabetes mellitus (T2DM). Materials and Methods. We included 132 subjects (88 men) with a mean age of 64.57 years and median T2DM duration of 14.5 years. Skin AGEs were measured with AGE reader mu connect (Diagnoptics) on the dominant arm. The device enables single and automated triplicate measurements: both of these were performed. DSPN was diagnosed through the neuropathy disability score (NDS). Small nerve fibre function was assessed by temperature and pinprick sensation on the foot. Bilateral measurement of the vibration perception threshold (VPT) on the hallux was carried out by using a neurothesiometer (Horwell Scientific Laboratory Supplies). Results. Single and triplicate AGE measurements were positively correlated with each other (Pearson’s correlation coefficient r=0.991, 95%CI=0.987-0.994, p<0.001). AGEs were higher among subjects with vs. those without DSPN (p<0.001). Furthermore, they were higher among subjects with reduced vs. normal temperature sensation (p<0.001), among subjects with reduced vs. normal pinprick sensation (p=0.002), among those with abnormal vs. normal monofilament examination (p<0.001), and among those with abnormal vs. normal VPT (p<0.001). AGEs were correlated with NDS, VPT, and monofilament score. Conclusions. In T2DM, skin AGEs are increased in the presence of DSPN. This holds true both for large and for small nerve function impairment. Moreover, AGEs are correlated with DSPN severity.